The relationship between SIRT1 and inflammation: a systematic review and meta-analysis - Sun, Haiyang; Li, Dong; Wei, Chaojie; Liu, Liping; Xin, Zhuoyuan; Gao, Hang; Gao, Rong (Frontiers in Immunology, 2024)
Recent studies underscore the anti-inflammatory role of SIRT1; however, its levels during inflammatory states remain ambiguous. We synthesized relevant studies up to 20 March 2024 to evaluate the relationship between SIRT1 and inflammation, using data from three major databases. Employing a random-effects model, we analyzed both cross-sectional and longitudinal studies, calculating weighted mean differences (WMDs) for pooled effect sizes. Subgroup and sensitivity analyses, along with a risk of bias assessment, were also conducted. We reviewed 13 publications, encompassing 21 datasets and 2,028 participants. The meta-analysis indicated higher SIRT1 levels in inflammatory groups compared to control groups pre-adjustment (WMD, 3.18 ng/ml; 95% CI 2.30, 4.06 ng/ml; P<0.001; I²= 99.7%) and post-adjustment (WMD, 0.88 ng/ml; 95% CI 0.14, 1.62 ng/ml; P<0.001; I²= 99.5%). Notably, middle-aged patients with inflammation exhibited lower SIRT1 levels (WMD, −0.85 ng/ml; 95% CI −1.47, −0.22 ng/ml; P= 0.008; I²= 95.4%), while groups characterized by East Asian descent, plasma studies, autoimmune conditions, and musculoskeletal disorders showed higher levels. The findings suggest that inflammation generally upregulates SIRT1, potentially elucidating its role in immunobiological processes. However, the significant heterogeneity observed, partly due to the cross-sectional nature of some data, limits insights into the duration of disease progression, which remains highly variable.